2005
DOI: 10.1158/1078-0432.ccr-05-1096
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Multidrug Resistance–Associated Proteins Predicts Prognosis in Childhood and Adult Acute Lymphoblastic Leukemia

Abstract: Purpose: Patients with acute lymphoblastic leukemia (ALL) are treated with a variety of chemotherapeutic drugs, which can be transported by six multidrug resistance^associated proteins (MRP). These MRPs have strongly overlapping functional activities. The aim of this study was to investigate the expression levels of MRP1to MRP6 and study their effect on prognosis. Experimental Design: The mRNA expression levels of MRP1 to MRP6 were analyzed by quantitative real-time PCR in leukemic blasts of105 de novo ALL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 27 publications
5
59
0
1
Order By: Relevance
“…For P-gp /ABCB1, we confirmed that also activity was increased while other transporter activities have not been assessed. It is not imperative, that mRNA levels translate into protein or activity levels, although in the majority of cases, variations in transporter mRNA levels were associated with changes in the corresponding protein (40) or with altered function (7,35,36,40,41). Hence while a similar correlation for other transporters may be assumed, it has not been established by this study.…”
Section: Discussionmentioning
confidence: 59%
“…For P-gp /ABCB1, we confirmed that also activity was increased while other transporter activities have not been assessed. It is not imperative, that mRNA levels translate into protein or activity levels, although in the majority of cases, variations in transporter mRNA levels were associated with changes in the corresponding protein (40) or with altered function (7,35,36,40,41). Hence while a similar correlation for other transporters may be assumed, it has not been established by this study.…”
Section: Discussionmentioning
confidence: 59%
“…Benderra et al found the same results in adult patients with AML (14,15). MRP3 is also associated with drug resistance in childhood ALL (16,17).…”
mentioning
confidence: 61%
“…The only important difference was a higher number of patients with the chromosomal aberration inv (16) in the GR group (Table 1). However, the expression of ABCA3 was not associated with this inversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of P-gp and MRP1 was shown to correlate with short survival in patients with adult T-cell leukemia (9,10). However, over the last two decades, it has become evident that P-gp is not the only human ABC transporter that, at least in vitro, is able to confer resistance to clinically significant chemotherapeutic agents leading to MDR (1,3,(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%